Physical Activity and Self-Efficacy on Exercise among Elderly Retired Philippine Army: Basis for Policy-making on Physical Activity Program - Dahonan-Cuyacot, Joanne B.; Hussin, Marites C.; Cordova, Nelson A. (International journal of Rural Development, Environment and Health Research, 2023)
This study aimed to investigate the physical activity and the level of self-efficacy in relation to exercise among the retired Philippine Army based in the province of Zamboanga del Norte, Philippines during the months of May and June 2023. A quantitative descriptive-correlational design was utilized in the study. Data were gathered from 19 retired Philippine Army personnel during the Armed Forces Veteran Association- Zamboanga del Norte’s monthly meeting. Frequency count, weighted mean and Pearson Correlation was used to analyze the collected data. The study found out that there was no significant relationship between physical activity on age, gender and length of service. It was also noted that there was a positive correlation between the variables age, gender and length of service this suggests that if there were changes in the variable physical activity, all other variables would change on the same direction. Moreover, Results showed that age and gender had a significant relationship as well as age and self-efficacy as both relationships showed a positive correlation. However, length of service and self-efficacy does not show significant relationship because of its negative correlation. Furthermore, results show no significant relationship between physical activity and the level of self-efficacy among Armed Forces veterans in Zamboanga del Norte. The results revealed a positive correlation which indicates that when the variable self-efficacy changes, the variable physical activity also changes on the same direction.